Diversification of business and technical efficiency of companies in Vietnam - Nguyen, Anh Phong; Nguyen, Anh Vu; Ho, Thi Hong Minh; To, Thi Thanh Truc (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
This study focuses on assessing the technical efficiency of enterprises across 63 provinces of Vietnam from 2015 to 2018 and the factors affecting their technical efficiency, in which we focus on two factors: business diversification and ICT index. In this research, we use the DEA method to group effective and ineffective enterprises, then use the GMM method to estimate the factors affecting to the firm’s performance. The research results show that the technical efficiency of enterprises in the provinces is quite small (about 10%), most of the enterprises have not achieved the technical efficiency due to the wasteful use of input factors. Research shows that business diversification and ICT both have a positive impact on efficiency, from which to increase technical efficiency, enterprises in provinces need to pay attention to business diversification and improve ICT index. in terms of the local government